Photometric analysis of the relationship between craniovertebral angle and facial profile in children aged 10–12 years - Maya Rosita; Sarworini B. Budiardjo; Mochamad Fahlevi Rizal (Saudi Dental Journal)
Background: Head posture deviation is seen in 52.5 % of children aged 6–15 years. Studies have shown that poor posture habits can impair muscle function during craniofacial growth and development. A muscle imbalance causes abnormal positioning of dental and skeletal structures, a condition that exerts negative impacts, such as changes in facial morphology. Objective: To determine through photometric analysis the relationship between craniovertebral angle as a function of head posture and glabella-subnasale-pogonion (G-Sn-Pg) angle as a function of facial profile in 10–12-year-old children, and the results will help to avoid facial development issues. Methods: Thirty-three subjects met the inclusion criteria. Their craniovertebral angles and facial profiles were measured using lateral photometry and ImageJ. The craniovertebral angle was determined by connecting the tragus and C7 with a horizontal line, whereas the facial profile angle was determined by connecting the glabella, subnasale, and pogonion. The relationship between the craniovertebral and G-Sn-Pg angle values was analyzed using the Pearson correlation test. Results: A significant relationship was observed between the craniovertebral angle and the G-Sn- Pg angle (p < 0.05), although such a relationship was weak (r = 0.373). Conclusion: A more forward head posture is associated with a more convex facial profile, and this relationship is useful for the early prevention and treatment.